Coworking as a flexible form of organization of the working space of the company - I. A. Vladimirov (Путеводитель предпринимателя)
In the article coworking is studied as a new form of organization of the company in modern conditions of globalization and post-industrialism. Key features and characteristics of coworking are considered. The practice of coworking application in the Russian organization and the problems arising during its implementation are analyzed. Practical recommendations for negative outputs elimination ofcoworking implementation are proposed.